Effects of Laparoscopic Roux-en-Y Gastric Bypass for Type 2 Diabetes Mellitus: Comparison of BMI > 30 and < 30 kg/m(2) - Ke, Zhigang (Obes Surg, 2017)
BACKGROUND: Recently, many studies focused on type 2 diabetes mellitus (T2DM) patients with body mass index (BMI) < 30 kg/m(2) and suggested that those patients might benefit from Roux-en-Y gastric bypass (RYGB). However, evidence on its effectiveness to improve T2DM patients with BMI < 30 kg/m(2) is still lacking. The aim of this study is to explore whether T2DM patients with BMI < 30 kg/m(2) get similar surgical effect from RYGB compared with those patients with BMI > 30 kg/m(2). METHODOLOGY: Seventy patients with uncontrolled T2DM underwent laparoscopic RYGB from May 2010 to December 2015 in the GI Department of Daping Hospital. Weight, BMI, waist circumference, glucose, and lipid metabolic parameters were collected and evaluated at baseline and 1, 3, 6, 12, and 24 months postsurgery. Patients with BMI < 30 kg/m(2) were compared with those with BMI > 30 kg/m(2). RESULTS: Among the 70 patients, 47 (67.1%) BMI < 30 kg/m(2), and 23 (32.9%) BMI > 30 kg/m(2). Patients with BMI < 30 kg/m(2) are significantly older; they are female predominant and have longer duration of diabetes. The complete remission of T2DM was 28.2% of the BMI < 30 kg/m(2) group and 57.9% of the BMI > 30 kg/m(2) group (p = 0.029). There was no significant difference in the change of glucose and lipid metabolic parameters of both groups. FPG, 2hPG, and HbA1c% levels were significantly improved after 1 month (p < 0.05), and then remained essentially stable from the sixth month in both groups. CONCLUSIONS: The 2-year study has shown that RYGB is a safe and effective procedure in treating T2DM with BMI < 30 kg/m(2), although the complete remission of T2DM in the BMI < 30 kg/m(2) group is lower than the BMI > 30 kg/m(2) group.